2018
DOI: 10.1002/nau.23522
|View full text |Cite
|
Sign up to set email alerts
|

Limited accuracy of transurethral and periurethral intrasphincteric injections of cellular suspension

Abstract: Although majority of cell depots were administrated accurately into the urethral wall, the precise delivery of cells into EUS is limited regardless of injection method. The insufficient accuracy of cell delivery into EUS and cell suspension leakage can contribute to the low efficacy of cell therapy in human patients with SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Recently, two preclinical studies in large animal models of SUI treatment provided evidence that transurethral injections of cells failed to precisely deposit the cells at the tissue targeted. 15,21 In about half of the samples investigated, full penetration of the needle through the urethra was noticed resulting in total loss or misplacement of the cells on the outer rim of the urethra. 15 Unnoticed and unintended misplacement of the cell suspension may contribute to the various outcomes of SUI cell therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two preclinical studies in large animal models of SUI treatment provided evidence that transurethral injections of cells failed to precisely deposit the cells at the tissue targeted. 15,21 In about half of the samples investigated, full penetration of the needle through the urethra was noticed resulting in total loss or misplacement of the cells on the outer rim of the urethra. 15 Unnoticed and unintended misplacement of the cell suspension may contribute to the various outcomes of SUI cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Among other technical points, proof‐of‐precise cell injection in the urethral sphincter and verification of cell viability and functional activity during follow‐up is a challenge in a clinical situation. Recently, two preclinical studies in large animal models of SUI treatment provided evidence that transurethral injections of cells failed to precisely deposit the cells at the tissue targeted . In about half of the samples investigated, full penetration of the needle through the urethra was noticed resulting in total loss or misplacement of the cells on the outer rim of the urethra .…”
Section: Discussionmentioning
confidence: 99%
“…Such a precision of cell injection by needle requires exceptional skills, as the physician has only limited estimation of depth of needle penetration, especially when the urethra is moving during the procedure. Imaging of the urethra during the procedure by ultrasound and mechanical devices to control protrusion improve the situation considerably [13,15,16], but do not give sufficient clues to whether the needle is pointing towards the delicate sphincter complex or fully penetrating the urethra [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness of urethral bulking agents compared to sling surgery was doubted during a longer follow-up period of 15 months. Burdzinska and colleagues compared the accuracy between the transurethral and periurethral route of intrasphincteric injections of autologous cellular suspensions in goats [17]. Their investigation revealed that 2/3 of all injections could be located in the urethral wall, while less than 1/5 were found inside EUS muscle structures.…”
Section: Discussionmentioning
confidence: 99%